2020
DOI: 10.3390/jcm9020512
|View full text |Cite
|
Sign up to set email alerts
|

Evidences for Expression and Location of ANGPTL8 in Human Adipose Tissue

Abstract: The metabolism of triglycerides (TGs) is regulated, among others, by the lipoprotein lipase (LPL) that hydrolyses the TGs on endothelial cells. In turn, LPL is inhibited by the ANGPTLs family of proteins, such as ANGPTL3, 4, and, 8; the latter is the least known. In this work, we have tried to establish the expression and localisation of the Angiopoietin-like 8 (ANGPTL8) protein in the visceral adipose tissue (VAT) of morbid-obese and non-obese patients. 109 subjects (66 women and 43 men) undergoing laparoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…ANGPTL8/betatrophin has shown its considerable association with diabetes and obesity as well as various metabolic biomarkers in glucose and lipid homeostasis (Wang et al 2016;Abu-Farha et al 2017). This hormone is reported to be highly enriched in human and mouse liver and adipose tissues (Chen et al 2019;von Loeffelholz et al 2017;Catalano-Iniesta et al 2020;Akimoto et al 2019;Mysore et al 2017). Previous studies focused on the roles of ANGPTL8 as a hormone that directly works on the endocrine system, while hardly any evidence showed that external mediators are involved in these processes (Siddiqa et al 2017;Wang et al 2016;Abu-Farha et al 2017;Wang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANGPTL8/betatrophin has shown its considerable association with diabetes and obesity as well as various metabolic biomarkers in glucose and lipid homeostasis (Wang et al 2016;Abu-Farha et al 2017). This hormone is reported to be highly enriched in human and mouse liver and adipose tissues (Chen et al 2019;von Loeffelholz et al 2017;Catalano-Iniesta et al 2020;Akimoto et al 2019;Mysore et al 2017). Previous studies focused on the roles of ANGPTL8 as a hormone that directly works on the endocrine system, while hardly any evidence showed that external mediators are involved in these processes (Siddiqa et al 2017;Wang et al 2016;Abu-Farha et al 2017;Wang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The angiogenin-like protein family includes eight members structurally similar to angiogenin and widely participate in the regulation of lipid metabolism, inflammation, haematopoietic stem cell activity and cancer cell invasion. ANGPTL8 is highly enriched in the human liver and various adipose tissues, whose levels were much lower in the other tissues, and recent studies suggested that ANGPTL8 showed similar tissue distribution in mice (Chen et al 2019;von Loeffelholz et al 2017;Catalano-Iniesta et al 2020;Akimoto et al 2019;Mysore et al 2017). ANGPTL8 has been reported to play a significant role in various metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…ANGPTL8 is mainly produced by the liver, but also by gut epithelium and adipose tissue [ 65 , 66 ]. While liver-derived ANGPTL8 is largely secreted in plasma, produced by adipocytes, remains intracellularly, particularly localized in nucleoplasm [ 67 , 68 , 69 ]. It is a small protein of 198 residues, capable of interaction with ANGPTL3, but exposing a coiled-coil domain only [ 7 , 70 ].…”
Section: Angptlsmentioning
confidence: 99%
“…A specific transcription factor for ANGPTL8 is the carbohydrate-responsive element-binding protein (ChREBP), which is induced by insulin stimulation [ 91 ]. While hepatocyte-derived ANGPTL8 is mainly secreted, in WAT and BAT it remains in nucleoplasm [ 69 ]. According to this model, ANGPTL8 is secreted in complexes with ANGPTL3, thus inhibiting LPL in oxidative tissues and directing dietary TGs to adipose tissue for storage [ 7 , 70 ].…”
Section: Angptlsmentioning
confidence: 99%
See 1 more Smart Citation